(untitled) (International Journal of Engineering and Computer Science, 2025)
Urbanization and greenhouse gas accumulation have intensified global temperature trends, with the Urban Heat Island (UHI) effect significantly impacting cities. In AMAC, landscape indices revealed moderate vegetation cover, with green spaces concentrated in Karshi, Gwi, and the National Arboretum, while built-up areas in Lugbe, Garki, and Wuse exhibited lower NDVI values. MNDWI analysis showed limited water bodies, with key blue spaces like Jabi Lake and the Gurara and Usuma rivers. Land Surface Temperature (LST) analysis from Landsat 8 imagery showed temperatures ranging from 30.36°C to 49.50°C, with an average of 40.93°C. Vegetated and water-covered areas exhibited lower temperatures due to evapotranspiration, while built-up zones experienced higher temperatures. UTFVI analysis identified thermal hotspots, with Karu, Gwagwa, and Gwi recording the highest temperatures, while the city center, Garki, and Wuse were cooler due to green and blue spaces. Jabi Lake exhibited the strongest cooling effect, with temperatures rising from 29.73°C at the lake to 40.74°C at 300 meters away. Zonal statistics confirmed the critical role of green and blue spaces in mitigating urban heat. These findings emphasize the need for urban planning strategies that expand and preserve green and blue spaces to combat the UHI effect and enhance climate resilience in AMAC.